The thick-billed murre (Uria lomvia) in Northwest Greenland (Avanersuaq) relies on Arctic cod (Boreogadus saida) in a changing climate - Knud Falk; Flemming Ravn Merkel; Myrthe Bergsma; Kasper Lambert Johansen; Kaj Kampp; Aili Lage Labansen; Anders Mosbech; Maasannguaq Oshima; Caroline Bouchard (Arctic Science)
Considering seabirds as indicators of environmental change, we compared thick-billed murre (Uria lomvia (Linnaeus, 1758)) adult and chick diet in the North Water polynya region, NW Greenland, during 1997 and 2023. In the adult murre diet, fish accounted for 86% and 42% of food items by number, and 99% by wet mass (WM) in both 1997 and 2023. Arctic cod (Boreogadus saida (Lepechin, 1774)) was the most important prey, contributing 90% and 99% of WM in 1997 and 2023, respectively. In 1997 the murres ate mostly small 1-year-old cod but in 2023 they mainly took larger 2- and 3-year-old Arctic cod. In the chick diet, gadids contributed 71% and 86% of prey items brought to the chicks in 1997 and 2023, respectively, supplemented by sculpins and eelpouts in 1997. Capelin (Mallotus villosus (Müller, 1776)) increasingly occur in the area but did not appear in the murre diet. The study highlights a consistent reliance on Arctic cod, although with differences between sampling years in size of ingested specimens. We recommend continued monitoring of top predator diets, coupled with local knowledge, to understand the impacts of ongoing changes in the region.